Reliability of A Measuring Tape for Assessing Hip Adduction via Ober’s Test - Anthony D'Amico; Kevin Silva; Charla Bouranis; Katelyn Nicolay; Joseph Gallo (International Journal of Sports Physical Therapy)
# Background Hip adduction is typically assessed via Ober’s test, using a handheld goniometer or inclinometer. As an alternative, a measuring tape, is sometimes used for this purpose in clinical settings, but there is currently no evidence to support this method’s reliability. # Purpose